PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL: STUDI EMPIRIS PADA PERUSAHAAN YANG TERCATAT DI BURSA EFEK INDONESIA - PARTONO , WELLIAM (Berkala Ilmiah Mahasiswa Akuntansi)
The information about company is essential for stakeholder. One of them that most requested is corporate social responsibility disclosure. Corporate social responsibility disclosure was representation by corporate social responsibility disclosure that refers to GRIGuidelines. This research examines the effect of some company characteristics, such as company size, profile, size of board of commissioner, leverage, and audit committee to corporate social responsibility disclosure. The sample was appointment with purposive sampling method. The population is 397 and 402 companies, which are listed at Indonesia Stock Exchange (IDX) in 2009 and 2010. The 286 corporate annual reports were analyzed as a sample. The results indicate that company size and profile have a significant positive influence on the corporate social responsibilit disclosure, but l everage, size of board of commissioner, and audit committee failed to show its significant effect.